Prevalence of traditional bullying and cyberbullying among children and adolescents in Australia: A systematic review and meta-analysis. (September 2019) - Jadambaa, Amarzaya; Thomas, Hannah J; Scott, James G; Graves, Nicholas; Brain, David; Pacella, Rosana
Background: Despite increased awareness of the adverse impact of bullying on mental health, the prevalence of bullying in Australia is uncertain. The aim of the current study was to conduct a systematic review and meta-analysis to estimate the prevalence of bullying (traditional and cyber) among Australian children and adolescents. This study synthesised bullying prevalence studies on victimisation experiences (being bullied) and perpetration experiences (bullying others) . Method: A systematic review of electronic databases (A+ Education, EMBASE, ERIC, PubMed, PsycINFO and Scopus up to 27 May 2017) was conducted. In addition, reference lists of included studies, theses recorded at the National Library of Australia, and government websites were surveyed to identify local area data as well as state and nationally representative data. Overall, 898 studies were screened and out of the 126 studies assessed for eligibility, 46 satisfied the pre-determined inclusion criteria. Meta-analyses based on quality-effects models generated pooled prevalence estimates for each of the two types of bullying involvement (victimisation and perpetration), as well as distinct models for traditional bullying and cyberbullying experiences by the type of involvement. Results: Overall, the 12-month prevalence of bullying victimisation was 15.17% (95% confidence interval = [9.17, 22.30]) and perpetration was 5.27% (95% confidence interval = [3.13, 7.92]). The lifetime prevalence for traditional bullying victimisation was 25.13% (95% confidence interval = [18.73, 32.11]) and perpetration was 11.61% (95% confidence interval = [7.41, 16.57]). Cyberbullying victimisation and perpetration were less common with lifetime prevalence of 7.02% (95% confidence interval = [2.41, 13.54]) and 3.45% (95% confidence interval = [1.13, 6.84]), respectively. Conclusion: Bullying is common among children and adolescents in Australia. There is a need to improve the measurement of bullying using a standardised instrument and for prevalence estimates to be collected on a regular basis to assess change over time. Wide implementation of anti-bullying programmes in Australian schools is a viable public health approach for the prevention of mental health problems.